Multi-model effective radiative forcing of the 2020 sulfur cap for shipping - R. B. Skeie; R. Byrom; Ø. Hodnebrog; C. Jouan; G. Myhre (Atmospheric Chemistry and Physics)
New regulations of sulfur emissions from shipping were introduced in 2020, reducing emissions of SO2 from international shipping by ∼ 80 %. As SO2 is an aerosol precursor, this drop in emissions over the ocean will weaken the total aerosol effective radiative forcing (ERF) that has historically masked an uncertain fraction of the warming due to the increased concentration of greenhouse gases in the atmosphere. Here, we use four global climate models and a chemical transport model to calculate the ERF resulting from an 80 % reduction in SO2 emissions from international shipping relative to 2019 emission estimates. The individual model means range from 0.06 to 0.09 W m−2, corresponding to the ERF resulting from the increase in CO2 concentration over the last 2 to 3 years. The full uncertainty in the ERF due to the new regulation is not quantified but will very likely be high considering the contribution of uncertainties in shipping SO2 emissions, the sulfur cycle, the modelling of cloud adjustments and the impact of interannual variability on the method for calculating radiative forcing.